1992
DOI: 10.1115/1.2899417
|View full text |Cite
|
Sign up to set email alerts
|

A Viscoelastic Model for the Dynamic Behavior of Saturated Poroelastic Soils

Abstract: A viscoelastic model is proposed to describe the dynamic response of the saturated poroelastic materials that obey the Biot theory (1956). The viscoelastic model is defined from the velocity and attenuation of dilatational and distortional waves in poroelastic materials. Its material properties are defined in terms of the elastic moduli, porosity, specific gravity, degree of saturation, and permeability of the soils. The proposed model is tested by comparing its response with the one of poroelastic materials i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…Figure 7(b) shows some discrepancies between results obtained with a two-phase poroelastic material and the approximate viscoelastic model for a sediment with extremely high permeability (k = 10 m=s). A similar conclusion was reached by Bardet [19]. Results presented in the following correspond to a permeability value of k = 10 −3 m=s.…”
Section: Simpliÿed Sediment Modelssupporting
confidence: 78%
See 1 more Smart Citation
“…Figure 7(b) shows some discrepancies between results obtained with a two-phase poroelastic material and the approximate viscoelastic model for a sediment with extremely high permeability (k = 10 m=s). A similar conclusion was reached by Bardet [19]. Results presented in the following correspond to a permeability value of k = 10 −3 m=s.…”
Section: Simpliÿed Sediment Modelssupporting
confidence: 78%
“…Thus the model accurately represents the e ects of the P1-and S-waves and ignores the P2-waves. Bardet [19] presented a Kelvin-Voigt viscoelastic model with linear frequency dependency of dissipation. Instead of the frequency dependency, the present model is based on the actual values of real and imaginary (damping) parts of the wave velocities, computed at each frequency for the porous material.…”
Section: Simpliÿed Sediment Modelsmentioning
confidence: 99%
“…22,23,32 Additionally, Bardet demonstrated that an equivalent viscoelastic model can be derived by equating expressions for VE energy storage and attenuation with the analogous PE expressions. 33 The VE equivalent model closely matched PE behavior except in certain conditions, including when the actuation period is on the same order as the fluid equilibration time, 34 approximated by…”
Section: C Choice Of Model For Brain Tissuementioning
confidence: 99%
“…The interested reader can refer to [40,41,47] as well as the references therein for more information of the model's historical backgrounds and examples of its application in soil dynamics. It is interesting to note that the author in [13] showed that the Kelvin-Voigt model can be used to describe the dynamic response of the saturated poroelastic materials https://www.cambridge.org/core/terms. https://doi.org/10.4208/aamm.…”
Section: The Kelvin-voigt Modelmentioning
confidence: 99%